Comércio interno e manufaturas nos tempos da Independência do Brasil - Ribeiro, Maria Alice Rosa (Revista USP, 2022)
The article discusses the theme of domestic trade and manufacturing during the Independence period. In the first part, we address the domestic trade - the slave trade, distinguishing the traders of the Atlantic trade from those who were active in the distribution of slaves in the domestic market. We deal with the trade of food supplies and common manufactured goods carried out by muleteers, sales, and the trade of more sophisticated imported manufactured goods. In the second part, the focus is on manufacturing production, the domestic craft industry, based on the processing of raw materials, cotton, food, beverages, pottery, ceramics, etc. Finally, it addressed one of the most important industrial activities, the ironworks, and the steel industry.